Immunohitochemical expression of p53 in human colocrectal carcinoma - abdulwahab Mirza, Sazan; Hassan AL-Tai, Tharwa H.; shaker, Hind H. (Journal of the Faculty of Medicine Baghdad, 2016)
Background:- Colorectal carcinoma is the most common cancer after the breast cancer in female and bronchus cancer in male. P53 is a tumor suppressor gene, approximately half of colorectal cancers present mutation in p53 gene. Objectives:- To determine the frequency and the pattern of p53expression in colorectal carcinoma by immunohistochemical technique and to correlate this expression with different clinicopathological parameters. Materials and methods:-Thirty cases of colorectal carcinoma were included in this study, these cases were diagnosed in private pathology laboratories in Baghdad / Iraq from January 2015 to Jaune 2015. Clinicopathological parameters such as age , gender , pathological diagnosis , including the tumor site , lymph nodes status , grade and stage of tumor were taken from patients files.Sections of 4μm stained by hematoxylen and eosin stain and immunohistochemical stained for p53. Results: Nineteen (63.3%) of the cases were males, 11(36.7%) cases were females, with age distribution ranging from (39-89) years with a mean age of 56.5 years . Ten cases(33.3%) located in the cecum , 3(10%)cases from each right colon , sigmoid 8 (26.7%) cases were from left colon and 6(20%) cases were from the rectum. Histologically the tumor grade range from moderately differentiated in 27 (90%) cases, and poorly differentiated in 3 (10%) cases. Regarding pathological staging (TNM system),2 (6.7%) cases were T2 ,24 (80%) were T3 , 4(13.3%) cases were T4. Lymph node involvement found in 14(46.7%) cases, and distant metastasis was found in 3(10%) cases. P53 expression was present in 11(36.7 %) cases, were distributed as follows:- weak in 1(3.3%) case,moderat in 3(10%) and marked in 7(23.4%) cases. There was no correlation between p53 expression and the clinicopathological parameters age , sex , histopathological grade, location , lymph nodes status and tumor stage. Conclusion: There was no significant statistical correlation between P53 expression by tumor and different clinicopathological parameters in this study